Issues of National Security and Human Rights in Nigeria: A Case Study of Islamic Movement of Nigeria - Nweke, Kenneth; Etido-Inyang, Eunice (Advances in Social Sciences Research Journal, 2020)
This paper examined issues of national security and human rights in Nigeria with emphasis on the conflicts between the federal government and the Islamic Movement of Nigeria (IMN). The objectives of the paper included to determine the nature of national security and human rights in Nigeria vis-à-vis the Islamic Movement of Nigeria; identity the contentious issues that triggered the conflicts and undermined national security and human rights between the federal government and the Islamic Movement of Nigeria; determine the implications of continued crackdown of IMN members and detention of their leader, El-Zakzaky and his wife on national security and human rights violations in Nigeria, and make necessary recommendations on how these issues can be amicably resolved without compromising national security and human rights of Nigerians, especially IMN members. This research has become imperative in view of the continued detention of Sheikh Ibrahim El-Zakzaky by the security operatives in Nigeria since 2015 in spite of court orders without concluding the trials. This has caused great concern to Nigerians with daily debates on the implications of this prolonged incarceration of the duo on national security and human rights in a democratic system of government. This paper was anchored on the “Family Theory in Clinical Practice”. The ‘Family Theory’ stressed the need to understand and consider the emotional functioning of a family or group as the basis for religious or political indoctrination, radicalisation, extremism and deviant behaviour that may be antagonistic to acceptable societal norms and values. This paper adopted descriptive research design. Data used for the study were gathered from secondary sources as content analysis was used in the interpretation of data. The paper found that the Islamic Movement of Nigeria (IMN) members were justified in their protest against military crackdown, detention and proscription. The paper observed that the over five year’s detention of Sheikh El-Zakzaky by the Nigerian government without trial amounts to the violation of his constitutionally guaranteed and legally protected human rights. This paper recommends the immediate and unconditional release of the Shiites leader from detention, speedy trial and respect for judicial pronouncements by the Nigerian government without compromising national security and human rights.